The role of CaH2 in preventing oxidation for the production of single-phase NiTi alloy in solid state - Mohd Zaki, Hafizah Hanim; Abdullah, Jamaluddin (Elsevier, 2016)
Single-phase NiTi synthesized from Ni and TiH2 powders was successfully formed in a solid-state reducing environment of CaH2. A comparison was done with a specimen synthesized in an environment without CaH2. An in-depth investigation on the surface of the specimen sintered without CaH2 revealed a thick layer of oxide with a thickness of 94 mm, whereas the specimen sintered in the reducing environment showed a significant reduction in oxide formation. The decomposition of CaH2 liberates Ca, which effectively reacts with oxygen at 930 C and consumes available oxygen in the system, thus minimizing oxygen to react with Ti to form TiO2. A significant reduction of this oxidation creates a balanced composition between Ni and Ti. An oxygen-free environment allows unhindered Ni-Ti reaction, which leads to the formation of single-phase NiTi, which is mostly found formed in the middle volume of the specimen. The optimum enthalpy change was observed to occur at the middle of the specimen with enthalpy change of 26 J/g on cooling and 25.5 J/g on heating, and the enthalpy was found to decrease towards the edge of the specimen due to the decreasing volume of transforming B2-NiTi.